Peranan Kepala Kampung Dalam Penyelesaian Sengketa Tanah Adat Di Kampung Lugom Distrik Yugungwi Kabupaten Lanny Jaya - James Yoseph Palenewen; Daniel Tanati; Marthinus Solossa (CV. Multi Kreasi Media, 2022)
Indigenous land disputes are not new anymore because in every region or area of customary law communities there are bound to be customary land disputes. Therefore this study aims to determine the role of the village head in resolving customary land disputes in Lugom Village, Yugungwi District, Lanny Jaya District and to determine the obstacles experienced by the village head in resolving customary land disputes in Lugom Village, Yugungwi District, Lanny Jaya District. The method used in this study is normative and empirical juridical, namely an approach that refers to legal norms contained in laws and regulations, library materials, written regulations or other legal materials that are secondary in nature and also looks at the facts that happened in the field. The results of this study reveal that the role of the village head in resolving customary land disputes in Lugom Village, Yugungwi District, Lanny Jaya Regency is very important with regard to the rights and obligations in the life of an indigenous community where a village head is required to be able to play an active role in holding his leadership so that he can manage community members properly, safely and regularly, if there are problems or disputes that occur among their customary communities, the village head acts as a mediator to resolve these problems or disputes, acts to restore peace within their customary communities and the factors that cause customary land disputes in the village Lugom, Yugungwi District, Lanny Jaya Regency, that is, there is overlapping customary land ownership whether the land is used for personal use, such as a place to live or shelter, or the land is used in groups or together, such as a place for farming and development. cattle stock, where fellow indigenous people claim that it is their land while the other party also states that the land is theirs, then a dispute arises over the customary land.